FEATURES OF MARKETING COMMUNICATIONS IN MODERN INNOVATIVE MARKETING - YANOVSKA, Viktoriia; TVORONOVYCH, Viktoriia; PYLYPENKO, Olena; USTILOVSKA, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the evolution of marketing from a simple sales tool to a complex, dynamic system that adapts to modern socio-cultural, economic and technological changes. The development of marketing is not linear and complete, but is a continuous process that reflects the transformation of interactions between market actors. Initially, marketing functioned as a linear transactional model, focused on a one-time exchange between producer and consumer. The modern paradigm, on the contrary, is based on a systems approach, where value is created as a result of interactions between different participants, such as companies, consumers, technological platforms and social communities. The article examines the role of marketing communications, which have become a decisive factor in competitiveness in the innovative marketing system. They form a positive image of the company and inform consumers about its offers. The main communication tools include advertising, sales promotion, PR, direct marketing, personal selling and trade marketing. The article highlights the transition from the classical functions of marketing (the 4P model: product, price, place, promotion) to the role of infrastructure for sensemaking and the formation of cultural narratives. This transformation is due to the growing importance of experience, emotional involvement and symbolic meanings. As a result, marketing becomes not so much a demand management as a formative force that creates space for mutual involvement and social influence. One of the key transformations is the transition to a relational concept of marketing, which emerged as a response to the limitations of the traditional transactional approach. The relationship between marketing communications and innovative marketing is two-way and interdependent. Marketing communications not only promote innovation, but also become innovative themselves.